2013
DOI: 10.1016/j.bbadis.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

IGF-II and IGFBP-6 regulate cellular contractility and proliferation in Dupuytren's disease

Abstract: Dupuytren's disease (DD) is a common and heritable fibrosis of the palmar fascia that typically manifests as permanent finger contractures. The molecular interactions that induce the development of hyper-contractile fibroblasts, or myofibroblasts, in DD are poorly understood. We have identified IGF2 and IGFBP6, encoding insulin-like growth factor (IGF)-II and IGF binding protein (IGFBP)-6 respectively, as reciprocally dysregulated genes and proteins in primary cells derived from contracture tissues (DD cells).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Increased β-catenin accumulation [17,19] and IGF2 expression [18] have been previously identi ed in DD tissue and primary broblasts compared with controls from adjacent, phenotypically non-brotic palmar fascia. As FSS and DD are clinically associated [3,20], we were interested to see if these characteristics were common to both connective tissue broses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased β-catenin accumulation [17,19] and IGF2 expression [18] have been previously identi ed in DD tissue and primary broblasts compared with controls from adjacent, phenotypically non-brotic palmar fascia. As FSS and DD are clinically associated [3,20], we were interested to see if these characteristics were common to both connective tissue broses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to its well-established roles in promoting cancer growth [30][31][32][33], relatively little is known about the roles of IGF-II in benign broproliferative diseases like FFS and DD. In addition to DD [18], IGF2 expression and IGF-II levels are reported to be increased in systemic sclerosisassociated pulmonary brosis [34]. IGF-II can act in combination with TGF-β1 signalling intermediates to promote myobroblast development in vitro [35] and both IGF-II and TGF-β1 can independently induce β-catenin translocation to the nucleus during epithelial mesenchymal transition (EMT) [36]; a process implicated in both cancer and brosis development [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study suggested that IGFBP-6 inhibited fibroblast proliferation by both IGF-dependent and -independent mechanisms (Raykha, et al 2013). Additionally, IGFBP-6-induced apoptosis appeared to be IGF-dependent (Hale, et al 2000) and IGF-independent (Iosef, et al 2008;Sueoka, et al 2000b) in different cell lines.…”
Section: Igf-independent Actionsmentioning
confidence: 99%